SURG-42. SAFETY OF INTRA-ARTERIAL CHEMOTHERAPY WITH OR WITHOUT OSMOTIC BLOOD BRAIN BARRIER DISRUPTION IN TREATMENT OF BRAIN TUMORS. (9th November 2020) - Uluc, Kutluay; Tabb, John Philip; Nerison, Caleb S; Dogan, Aclan; Priest, Ryan A; Ambady, Prakash; Neuwelt, Edward
Abstract: BACKGROUND: Intra-arterial route of drug delivery (IA) without or with osmotic blood brain barrier disruption (IA/BBBD) is one of the available techniques to overcome the blood-brain barrier and enhance drug delivery to brain tumors. We present a large single institution safety data of IA or IA/BBBD. METHODS: This is a retrospective review of the electronic records, imaging and complications in patients who underwent IA or IA/BBBD in OHSU between December, 1997 and November, 2018. Procedural complications were documented prospectively and reviewed in the electronic medical records. Toxicities, attributed to chemotherapy, were reported when grade is either II or higher by Common Terminology Criteria for Adverse Events (CTCAE). RESULTS: Complications related to chemotherapy and procedure were reported separately. Total of 4940 procedures (1102 IAC and 3838 oBBBD) were performed on 436 patients (190 female and 246 male). Pathologies were primary central nervous system lymphoma (PCNSL) (n=115, 26%), secondary central nervous system involvement (SCNSL) (n=37, 8%), glioblastoma (n=79, 18%), astrocytoma (grade II/III) (n=34, 7%), oligodendroglioma (n=64, 14%), pilocytic astrocytoma (n=10, 2%), metastatic (n=38, 8%), embryologic (n=37, 8%), others (n=22, 5%). Procedural complications: groin related (n=16, 0.32%), transient neurological decline (n=57, 1.15%), subintimal arterial injury (n=13, 0.26%), asymptomatic imaging changes (T2 or DWI) (n=60, 1.21%), symptomatic stroke (n=21, 0.43%), myocardial infarction (n=3, 0.37%), cervical cord injury (n=6, 0.12%), death within 3 days (n=6, 0.12%). Minor complications are 2.86%, major complications are 1.12%. Eighty-four percent (n=369) of the patients experienced grade 2 or higher toxicities attributed to chemotherapy. CONCLUSION: We present the largest safety data set to date from a single institution experience using IA and IA/BBBD for brain tumors. Our results suggest that IA and IA/BBBD is safe and can be performed multiple times in the same patients with acceptable procedure related complications. Efficacy of this approach is being evaluated in prospective clinical trials.